Analysis of Translation Strategy in Transferring meaning of English Idiom into Bahasa Indonesia in the subtitle of Pitch Perfect 3 Movie - Destaria, Monicha; Rini, Yulan Puspita (English Education: Jurnal Tadris Bahasa Inggris, 2019)
Transferring meaning embedded by English idiom is not an easy way to do. The meaning contained by English Idiom cannot be comprehended by merely knowing the meaning from each word arranging the idiom. Dealing with English idiom in translation is quite hard because the translator has to transfer the meaning of English idiom into Bahasa Indonesia rightly. On the other hand, it is quite difficult to find the equivalence term in Bahasa Indonesia reflecting the same meaning as it is reflected in the source text. To manage this problem, the translation strategies need to be applied. This research focuses on analyzing the translation strategies used by the translator in transferring the meaning of English idioms into Bahasa Indonesia in the subtitle of  Pitch Perfect 3 Movie. The research method is descriptive qualitative method.. Baker’s translation strategies is used as guideline in classifying the translation strategies used. After finding the type of translation strategies employed, further identifying whether the meaning of English idiom is transferred rightly in Bahasa Indonesia. According to the finding, translation by using idiom in similar meaning and disimilar form was not used by the translator to translate the idioms. The frequency of  translation by using idiom in similar meaning but disimilar form strategy is 4 idioms. 46 idioms were translated by using paraphrased strategy. It is only 1 idiom was translated by using omission strategy. that the meaning of 36 idioms are transferred accurately. The meaning of four idioms were transferred Less-accurately. The meaning of 11 idioms were classified as inaccurate translation